Bridging the gap between scientists and clinicians: addressing collaboration challenges in clinical AI integration - Mia Gisselbaek; Joana Berger-Estilita; Arnout Devos; Pierre Luigi Ingrassia; Peter Dieckmann; Sarah Saxena (BMC Anesthesiology)
Abstract This article explores challenges for bridging the gap between scientists and healthcare professionals in artifical intelligence (AI) integration. It highlights barriers, the role of interdisciplinary research centers, and the importance of diversity, equity, and inclusion. Collaboration, education, and ethical AI development are essential for optimizing AI’s impact in perioperative medicine.